Augmented Reality Pengenalan Senjata Tradisional Indonesia Timur: Augmented Reality Introduction Of Eastern Indonesian Traditional Weapons - Steven Rahaweman; Arie S. M. Lumenta; Arthur M. Rumagit (Universitas Sam Ratulangi, 2023)
Abstract — Traditional weapons are one part of the cultural heritage that we must protect. Because of the importance of local culture as identity, all levels of society must have a sense of responsibility to protect and apply local wisdom, especially the creation of youth, even though they are dealing directly with globalization. Based on the results of the questionnaire from the respondents, it was shown that only a small proportion had in-depth knowledge of traditional weapons, 83.3% answered that the knowledge of traditional weapons was very important as a cultural heritage that we must protect. So far, they have learned about traditional weapons through the internet, books, and museums. As many as 68.9% of respondents said that learning through the media is less interactive, boring, and explanations do not explain a nd there are some places that do not have museums. For this reason, it is necessary to have learning media that can be used mobile, because many people have smartphones. One of the learning media used mobile-based is augmented reality technology. This research aims to design an augmented reality application for the introduction of traditional eastern Indonesian weapons designed using the multimedia development life cycle method. Based on the test results, it was obtained that the user's knowledge of traditional weapons in eastern Indonesia increased with interesting learning. Key words— 3D, AR Camera, Augmented Reality, Indonesia East Traditional Weapons Abstrak — Senjata Tradisional adalah salah satu bagian dari warisan budaya yang harus kita jaga. Karena begitu pentingnya budaya lokal sebagai jati diri, semua lapisan masyakarat harus mempunyai rasa tanggung jawab untuk melindungi dan melestarikan kearifan lokal terlebih khususnya generasi muda meskipun berhadapan langsung dengan globalisasi. Berdasarkan hasil kuesioner dari sejumlah responden menunjukkan hanya sebagian kecil yang memiliki pengetahuan mendalam tentang senjata tradisional, 83,3% menjawab sangat pentingnya pengetahuan senjata tradisional sebagai warisan budaya yang harus kita jaga. Selama ini mereka belajar tentang senjata tradisional ada yang melalui internet, buku, dan museum. Sebanyak 68,9% responden mengatakan pembelajaran melalui media tersebut kurang interaktif, membosankan, kurang menarik dan penjelasan yang tidak terperinci serta ada beberapa tempat yang tidak memiliki museum. Untuk perlu adanya media pembelajaran yang bisa digunakan secara mobile, dikarenakan sudah banyak masyarakat yang memiliki smarthpone. Salah satu media pembelajaran yang digunakan berbasis mobile adalah teknologi augmented reality. Penilitian ini bertujuan merancang aplikasi augmented reality pengenalan senjata tradisional indonesia timur dirancang dengan metode multimedia development life cycle. Berdasarkan hasil pengujian didapatkan peningkatan pengetahuan pengguna terhadap senjata tradisional indonesia timur dengan pembelajaran yang menarik. Kata kunci — 3D, Indonesia Timur, Realitas Tertambah, Senjata Tradisional, Kamera AR